Observations of Aerosol‐Cloud Interactions During the North Atlantic Aerosol and Marine Ecosystem Study. Issue 3 (7th February 2020) - Sinclair, Kenneth; van Diedenhoven, Bastiaan; Cairns, Brian; Alexandrov, Mikhail; Moore, Richard; Ziemba, Luke D.; Crosbie, Ewan
Abstract: Clouds and their response to aerosols constitute the largest uncertainty in our understanding of 20th‐century climate change. We present an investigation that determines linkages between remotely sensed marine cloud properties with in situ measurements of cloud condensation nuclei (CCN) and meteorological properties obtained during the North Atlantic Aerosols and Marine Ecosystems Study. The first two deployments of this campaign have geographically similar domains but occur in different seasons allowing the response of clouds to a range of CCN concentrations and meteorological conditions to be investigated. Well‐defined connections between CCN and cloud microphysical properties consistent with the indirect effect are observed, as well as complex, nonlinear secondary effects that are partially supported by previously proposed mechanisms. Using the Research Scanning Polarimeter's remotely sensed effective variance parameter, correlation is found with liquid water path. In general, cloud macrophysical properties are found to better correlate with atmospheric state parameters than changes in CCN concentrations. Key Points: Cloud microphysical property changes are found to correlate with marine biogenic aerosol concentrations A strong correlation is found between cloud droplet number concentrations and cloud condensation nuclei concentrations The width of the cloud droplet distribution is found to be more strongly correlated with cloud liquid water path than droplet concentration